An analysis of interpretation of hadith “whoever changes his religion, kill him" - Gilani, Sayyid Muhammad Yunus (s.n, 2012)
As long as Islam was in power, there was no problem in understanding the views and opinions of the main stream of Islam represented by the Jamhur 'Ulama'. Onc the power passed into the Islamically weaker hands, the anti-Islamic elements worked for its detriment, with all their abilities and capacities, causing Islam being criticized to the basic and essential judicial sources, core and non-core as well. The critics of Islam triggred some Shariah issues, some of them needed to be checked out, but the most of them were raised either because of hostility towards Islam or because of misunderstandings. Among these issues was the issues, was the issue of freedom.